Chitin Attenuates Expression of Listeria monocytogenes Virulence Genes in vitro - Villoria Recio, Miguel; Lee, Bo-Hyung; Lillebæk, Eva Maria Sternkopf; Kallipolitis, Birgitte H.; Gahan, Cormac G. M.; Ingmer, Hanne; Larsen, Marianne Halberg (Frontiers in Microbiology, 2020)
External signals are crucial for bacteria to sense their immediate environment and fine-tune gene expression accordingly. The foodborne pathogen Listeria monocytogenes senses a range of environmental cues in order to activate or deactivate the virulence-inducing transcriptional factor PrfA during transition between infectious and saprophytic lifecycles. Chitin is an abundant biopolymer formed from linked β-(1–4)-N-acetyl-D-glucosamine residues associated with fungi, the exoskeleton of insects and often incorporated into foods as a thickener or stabiliser. L. monocytogenes evolved to hydrolyse chitin, presumably, to facilitate nutrient acquisition from competitive environments such as soil where the polymer is abundant. Since mammals do not produce chitin, we reasoned that the polymer could serve as an environmental signal contributing to repression of L. monocytogenes PrfA-dependent expression. This study shows a significant downregulation of the core PrfA-regulon during virulence-inducing conditions in vitro in the presence of chitin. Our data suggest this phenomenon occurs through a mechanism that differs from PTS-transport of oligosaccharides generated from either degradation or chitinase-mediated hydrolysis of the polymer. Importantly, an indication that chitin can repress virulence expression of a constitutively active PrfA* mutant is shown, possibly mediated via a post-translational modification inhibiting PrfA* activity. To our knowledge, this is the first time that chitin is reported as a molecule with anti-virulence properties against a pathogenic bacterium. Thus, our findings identify chitin as a signal which may downregulate the virulence potential of the pathogen and may provide an alternative approach towards reducing disease risk.